I believe this is the answer.
Two ways:
1) guess factors(trial and error)
2) use quadratic formula.
If you use this method then a = -3, b = -6 and c = -1
x = -b +/- [sqrt(b^2 -4ac)/2a]
substituting a, b, and c into our equation we get:
x = - (-6)+/- [sqrt ((-6)^2) - 4(-3)(-1))/2 (-3)]
x = + 6 +/- [sqrt (36 -4 (3)/-6)] if I didnt make a mistake in my signs
x = + 6 +/- [sqrt (36 -12)/-6)]
x = 6 +/- [sqrt (24)/-6] but sqrt 6 x sqrt of 4 = sqrt 24 hence
x = 6 +/- [ sqrt 6 x sqrt 4 /-6] that is:
x = 6 +/- [sqrt 6 x 2 /-6 ]
so x = 6 + [sqrt 6 x 2/-6] and x = 6 - [sqrt 6 x 2/-6]
Answer is in the picture:
Answer: this is Judy Heckman you answered a question about a parabola graph and someone went off of it before I could study it. Help thanks
Step-by-step explanation:
Answer:
This is easy -- it's just a list of steps. At this level, the problems are pretty simple.
Let's just do one, then I'll write out the list of steps for you.
Find the inverse of f( x ) = -( 1 / 3 )x + 1
STEP 1: Stick a "y" in for the "f(x)" guy:
y = -( 1 / 3 )x + 1
STEP 2: Switch the x and y
( because every (x, y) has a (y, x) partner! ):
x = -( 1 / 3 )y + 1
STEP 3: Solve for y:
x = -( 1 / 3 )y + 1 ... multiply by 3 to ditch the fraction ... 3x = -y + 3 ... ditch the +3 ... subtract 3 from both sides ... 3x - 3 = -y ... multiply by -1 ... -3x + 3 = y ... y = -3x + 3
STEP 4: Stick in the inverse notation, f^( -1 )( x )
f^( -1 )( x ) = -3x + 3
Step-by-step explanation: